Thea Astley's Failed Eden - Genoni, Paul (Cambridge Scholars Press, 2006)
In the critical attention given to Thea Astley's fiction there has been little written about her use of landscape. This is surprising because Astley is often identified as a 'regional writer' with a body of work that is strongly associated with coastal north Queensland, and there is little doubt that she evokes the landscapes of her novels as a memorable element within their drama.This paper suggests an approach to landscape as it is used by Astley, and in doing so argue that it is interconnected with both her characterisation and her moral positioning. The image she uses to forge this connection is the Garden of Eden, which is of course for Judeo-Christian cultures the iconic representation of both perfect physical beauty and an ideal moral state.